Priority in consumption of trees and shrubs by game ungulates in forests of Polissia and Forest-Steppe - Гулик , І. Т.; Шевчук , В. В.; Шейгас , І. М. (Forestry and Forest Melioration, 2023)
Introduction The total reserve of natural tree and shrub fodder in the pre-winter period is one of the most important indicators when assessing the quality of hunting areas and is very important in determining the optimal capacity of such areas for game ungulates, in particular for determining the optimal number of European roe deer in a specific area. However, the determination of the total reserve of this fodder is not enough to justify the optimal number of dendrophagous game ungulates in a specific area for hunting (optimal density). To determine this indicator, it is necessary to know the proportion and degree of damage caused by game ungulates to specific types of trees and shrubs in the critical for the animal winter period, that is, to determine the priority in their consumption of plants that serve them as forage. Materials and Methods During the study, we determined a total reserve of tree-shrub fodder for roe deer and other species of wild ungulates. Along with that, we assessed the priority in consumption, the proportion, and the degree of damage caused by European roe deer to various types of tree and shrub species in the coldest season in the forests of Polissia and Forest-Steppe in Ukraine. The research was conducted in hunting areas located in Zhytomyr and Ternopil regions in relatively poor, medium, and rich natural fodder areas, namely, in the Polissia Hunting Region: Korostyshivske State Forest Enterprise and Korostenske State Forest and Hunting Enterprise; and in Forest-Steppe Hunting Region: Berezhanske State Forest Enterprise, Buchaske State Forest Enterprise, Chortkivske State Forest Enterprise. All surveyed forests were divided into 12 separate groups depending on the dominant tree stand and the type of forest growth conditions. A total of 174 sample plots were laid out in the study areas. The food range of the European roe deer was taken into account up to a height of 1.2 m from the soil surface. When determining the total post-winter food reserve in the sample plots, the numbers of damaged food trees and shrubs of each species were simultaneously counted, which allowed us to define the browsing damage degree for each species. Results The study conducted in the forests of Polissia and Forest-Steppe in Ukraine showed the priority in consumption, the proportion and degree of damage caused by game ungulates to food trees and shrubs in winter on the example of European roe deer (Capreolus capreolus L.). The results obtained can be used to assess the suitability of lands for ungulates, and their forage capacity, to determine the quality class, to calculate the density of animals in the area, and also help to establish a list of priority feeding stations for roe deer during the coldest season. The research shows that the proportions of damaged food species of trees and shrubs in the same types of forest hunting areas were similar regardless of the hunting region (Polissia or Forest-Steppe) and the density of undergrowth in the sample plots. The performed calculations, their analysis, and generalization showed that the damage of the most consumed food plants during the winter period (hunger gap) of the year depends on the food species, the species composition of the dominant tree stand (coniferous, mixed, or deciduous), and the origin of the stand (native or derivative). Conclusions The proportion of food species damaged by wild ungulates in stands with various species composition depends on the ecological conditions of their growth. The distribution of food tree and shrub species according to fodder attractiveness for European roe deer and the damage degree is characteristic only for the cold period of the year and is of great importance for determining the consumption proportion for certain food species in a critical period in terms of fodder reserve. The analysis of the findings can be used to characterize the suitability of land for the habitat of European roe deer and other species of dendrophagous game ungulates, to assess the forage capacity of hunting areas for these species, and to evaluate the quality class of hunting areas. It also enables identifying a list of priority feeding stations for wild ungulates in the winter period. 1 Table, 10 Refs.